ANALISIS PENGELOLAAN KEUANGAN DIPA DALAM MENINGKATKAN KINERJA STAF DISKUAU DI DINAS KEUANGAN ANGKATAN UDARA TAHUN 2023 - Nugroho, Prasetyo; Sugihyanty, Eneng (Worksheet : Jurnal Akuntansi, 2025)
The management of DIPA (Daftar Isian Pelaksanaan Anggaran) plays a strategic role in ensuring the effectiveness of budget utilization within the Air Force Finance Office (DISKUAU). As an institution responsible for managing state finances, DISKUAU must uphold the principles of transparency, accountability, and efficiency in implementing DIPA to support staff performance and overall organizational operations. However, in practice, the implementation of DIPA still faces challenges such as regulatory complexity, limited human resources, and the lack of an integrated information system. This research aims to analyze how DIPA management can improve DISKUAU staff performance using a descriptive qualitative approach. Data is obtained through observations, interviews, and document studies regarding the implementation of DIPA within DISKUAU. The research findings indicate that optimizing information systems, providing more intensive staff training, and enhancing inter-unit coordination positively impact the effectiveness of budget management. With  better  financial   management,   DISKUAU staff  can  work more  productively, improve financial administration accuracy, and accelerate budget realization. Additionally, this research identifies several key obstacles in DIPA implementation, such as the limited capacity of human resources in understanding financial policies and the suboptimal use of technology. To address these challenges, DISKUAU is expected to increase technical training, develop a more integrated financial information system, and strengthen budget oversight mechanisms. The implications of this research highlight the need for continuous improvements in DIPA-based financial management systems to ensure optimal staff performance sustainability. Through system reforms and staff capacity enhancement, the effectiveness of DIPA implementation within DISKUAU can be maximized, allowing the organization to achieve its strategic goals